2011
DOI: 10.1111/j.1365-2885.2011.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic testing of marbofloxacin administered as a single injection for the treatment of bovine respiratory disease

Abstract: New approaches in Pharmacokinetic/Pharmacodynamic (PK/PD) integration suggested that marbofloxacin, a fluoroquinolone already licensed for the treatment of bovine respiratory disease at a daily dosage of 2 mg/kg for 3-5 days, would be equally clinically effective at 10 mg/kg once (Forcyl(®)), whilst also reducing the risk of resistance. This marbofloxacin dosage regimen was studied using mutant prevention concentration (MPC), PK simulation, PK/PD integration and an in vitro dynamic system. This system simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
1
35
0
2
Order By: Relevance
“…In addition to that in pigs, marbofloxacin pharmacokinetics have been investigated in other species. After intramuscular injection, the t 1/2λz was 1.96, 3.15, 3.65, 7.16, 7.72, and 17.50 h in ostriches [4], ducks [8], sheep [15], camels [11], rabbits [13], and calves [17], respectively. These results indicate that the elimination of marbofloxacin from pigs is slower than that in other species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that in pigs, marbofloxacin pharmacokinetics have been investigated in other species. After intramuscular injection, the t 1/2λz was 1.96, 3.15, 3.65, 7.16, 7.72, and 17.50 h in ostriches [4], ducks [8], sheep [15], camels [11], rabbits [13], and calves [17], respectively. These results indicate that the elimination of marbofloxacin from pigs is slower than that in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Ferren et al [34] suggested that even lower doses of marbofloxacin could potentially eradicate low counts (10 5  CFU/mL) in the lung, while having a minimal impact on the microbiota of the large intestine. On the other hand, Vallé et al [35] validated for the bovine pneumonia pathogens, P. multocida and Mannheimia haemolytica , the concept of a single high dose of marbofloxacin compared to a daily dose of 2 mg/kg for 3–5 days. A bactericidal effect against bovine P. multocida was achieved within one hour, when marbofloxacin was administered at five times the recommended daily dose (10 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Re-evaluation of antimicrobial dosage regimens, considering updated PK/PD requirements, constitutes a first step to limit the impact of antimicrobials on commensal floras. For example, recently in veterinary medicine, the marbofloxacin dosage regimen was re-evaluated for treatment of Gram negative infections and the current labeled dose of 10 mg/kg given in a single injection was added to the first label approved dosage of 2 mg/kg over 3–5 days, leading to a decrease in the time of residence of the drug in the body while maintaining clinical efficacy (Valle et al, 2012). Dosage regimens of existing drugs previously determined according to results of clinical trials can also be evaluated based on standard PK/PD concepts, as performed with tulathromycin in calves (Toutain et al, 2016b).…”
Section: Priority Actions To Minimize the Impact Of Veterinary Antimimentioning
confidence: 99%